Organic and Carbon Gels From Laboratory Synthesis to Applications - Arenillas, Ana; Menéndez, J. Angel; Reichenauer, Gudrun; Celzard, Alain; Fierro, Vanessa; Maldonado Hodar, Francisco José; Bailόn-Garcia, Esther; Job, Nathalie (Advances in Sol-Gel Derived Materials and Technologies, 2019)
This expert volume provides specialized coverage of the current state of the art in carbon gels. Carbon gels represent a promising class of materials with high added value applications and many assets, like the ability to accurately tailor their structure, porosity, and surface composition and easily dope them with numerous species. The ability to obtain them in custom shapes, such as powder, beads, monoliths, or impregnated scaffolds opens the way towards numerous applications, including catalysis, adsorption, and electrochemical energy storage, among others. Nevertheless, it remains a crucial question as to which design synthesis and manufacturing processes are viable from an economic and environmental point of view. The book represents the perspectives of renowned specialists in the field, specially invited to conduct a one-day workshop devoted to carbon gels as part of the 19th International Sol-Gel Conference, SOL-GEL 2017, held on September 3rd, 2017 in Liège, Belgium. Addressing properties and synthesis through applications and industry outlook, this book represents essential reading for advanced graduate students through practicing researchers interested in these exciting materials. Authored by experts at the forefront of the latest developments in the field Covers properties and synthesis to applications and industry Thoroughly multidisciplinary in authorship and outlook Practical and comprehensive advice for those exploring the possibilities of carbon gels.